INTEGRATION OF RISK MANAGEMENT SYSTEMS TO ENSURE ENTERPRISE SECURITY AND COMPETITIVE ADVANTAGES - HOROBKO, Roman; POSTOVIT, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In today's world, where the level of uncertainty and the number of risks are constantly increasing, the issue of security is becoming highly relevant to organizations in various industries. Integrating such systems into the organization's structure ensures an effective response to risks and is an important component of modern management. The paper examines the main approaches to integrating risk management systems that allow organizations to respond to potential threats promptly. Special attention is paid to the security mechanism, which guarantees promptness and efficiency of actions in response to identified risks. It is important that the integration of risk management systems not only reduces risks but also contributes to increasing the efficiency of the company's activities in conditions of rapid changes.Various approaches to risk management were considered during the research. Special attention is paid to strategies focused on risk management, including preventive measures and rapid response mechanisms. Preventive measures are key to preventing risks from occurring or reducing their impact. For example, they can be the introduction of new technologies or the improvement of internal processes to minimize potential technical failures. Quick response mechanisms, on the other hand, allow quick solutions to problems that arise, minimizing the negative consequences.The paper proposed an integrated risk management system that covers all levels of organizational management—from strategic to operational. This concept allows you to create a holistic security system considering long-term strategies and current operational processes. Integrating risk management at different levels ensures a balance between safety and economic efficiency in the decision-making process.Based on the analysis of the best risk management practices, several recommendations were developed for implementing adequate security mechanisms. The main emphasis is on adapting generally accepted methodologies to the specific conditions of each organization's activity. In addition, it was recommended that risk management policies and procedures be developed and implemented to provide a unified approach to identifying, assessing, and responding to risks.The study's results showed that the effective integration of risk management systems allows for significantly reduced risk levels and ensures the stable functioning of the organization even in conditions of high uncertainty.
Keywords: integration of risk management systems; security mechanism; risk monitoring; risk management; risk identification; risk minimization; automated systems; organizational security; preventive measures; crisis situations